2022
DOI: 10.1155/2022/1705193
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Analysis of the Oral Flora in Patients with Recurrent Aphthous Stomatitis

Abstract: The present study detected differences in the oral mucosal flora in healthy people and patients diagnosed with recurrent aphthous stomatitis (RAS) using the 16S ribosomal RNA high-throughput sequencing (rRNA-seq). All samples were collected from the lower lip mucosa of 100 healthy individuals and 100 patients with RAS. After the extraction, DNA was subjected to PCR amplification for the bacterial 16S rRNA gene, before subjecting to high-throughput sequencing, and matched to a database. Most bacterial species a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…75 Previous studies have shown that Proteobacteria exhibited a rising trend in the area of the mouth mucosa ulcer. 76 Also, it increased during the onset and progression of periodontitis, while the abundance of Firmicutes and Actinobacteria decreased. 77,78 Firmicutes are the primary beneficial bacteria in the saliva and buccal mucosa, 79 which is a huge bacterial phylum encompassing over 250 genera, including Lactobacillus, Faecalibacterium, Eubacterium, Roseburia and Anaerostipes.…”
Section: Food and Function Papermentioning
confidence: 97%
“…75 Previous studies have shown that Proteobacteria exhibited a rising trend in the area of the mouth mucosa ulcer. 76 Also, it increased during the onset and progression of periodontitis, while the abundance of Firmicutes and Actinobacteria decreased. 77,78 Firmicutes are the primary beneficial bacteria in the saliva and buccal mucosa, 79 which is a huge bacterial phylum encompassing over 250 genera, including Lactobacillus, Faecalibacterium, Eubacterium, Roseburia and Anaerostipes.…”
Section: Food and Function Papermentioning
confidence: 97%
“…Some subpopulations of Prevotella, Neisseria, and Streptococcus, such as Prevotella melaninogenicus , Neisseria lactamica , Neisseria mucosa , Neisseria saprophaga , Neisseria subflava , Streptococcus viridans , S. mutans , and S. aureus , may be related to the occurrence of RAU 108 . The significant increase in the number of Prevotella at the ulcer site more effectively indicates that Prevotella is closely related to RAU 109 . For Helicobacter pylori , there is still no direct evidence to prove that it is related to the occurrence and development of RAU 110 .…”
Section: Comparison Of the Main Microbiota Between Children And Adult...mentioning
confidence: 99%
“…108 The significant increase in the number of Prevotella at the ulcer site more effectively indicates that Prevotella is closely related to RAU. 109 For Helicobacter pylori , there is still no direct evidence to prove that it is related to the occurrence and development of RAU. 110 There is less research on viruses.…”
Section: Comparison Of the Main Microbiota Between Children And Adult...mentioning
confidence: 99%
“…One of the most prevalent conditions affecting the oral mucosa is recurrent aphthous stomatitis.Three kinds of the condition are distinguished clinically: minor, major, and herpetic form [ 1 ]. Minor aphthous lesions are less than 5 mm in size, circular, have a definite border, are painful, and heal without leaving scars in ten to fourteen days [ 2 ].…”
Section: Introductionmentioning
confidence: 99%